Die Ampel muss zum finanzpolitischen Pragmatismus zurückfinden! - Achim Truger (Wirtschaftsdienst, 2023)
– In this article, after a brief sketch of the fiscal strategy of the German Government and the current budgetary situation, it is first argued that the current budget dispute could have been avoided because the coalition essentially created the dispute through two fiscal (mid)decisions last year. Secondly, a few potential pragmatic solutions are pointed out.
Keywords: H62; E62; H68; H77; 330; Finanzpolitik; Öffentlicher Haushalt; Deutschland; Finanzpolitik; Öffentlicher Haushalt; Deutschland